FT-IR quantification of the carbonyl functional group in aqueous-phase secondary organic aerosol from phenols. (January 2015) - George, Kathryn M.; Ruthenburg, Travis C.; Smith, Jeremy; Yu, Lu; Zhang, Qi; Anastasio, Cort; Dillner, Ann M.
Abstract: Recent findings suggest that secondary organic aerosols (SOA) formed from aqueous-phase reactions of some organic species, including phenols, contribute significantly to particulate mass in the atmosphere. In this study, we employ a Fourier transform infrared (FT-IR) spectroscopic technique to identify and quantify the functional group makeup of phenolic SOA. Solutions containing an oxidant (hydroxyl radical or 3, 4-dimethoxybenzaldehyde) and either one phenol (phenol, guaiacol, or syringol) or a mixture of phenols mimicking softwood or hardwood emissions were illuminated to make SOA, atomized, and collected on a filter. We produced laboratory standards of relevant organic compounds in order to develop calibrations for four functional groups: carbonyls (CO), saturated C–H, unsaturated C–H and O–H. We analyzed the SOA samples with transmission FT-IR to identify and determine the amounts of the four functional groups. The carbonyl functional group accounts for 3–12% of the SOA sample mass in single phenolic SOA samples and 9–14% of the SOA sample mass in mixture samples. No carbonyl functional groups are present in the initial reactants. Varying amounts of each of the other functional groups are observed. Comparing carbonyls measured by FT-IR (which could include aldehydes, ketones, esters, and carboxylic acids) with eight small carboxylic acids measured by ion chromatography indicates that the acids only account for an average of 20% of the total carbonyl reported by FT-IR. Highlights: We employed an FT-IR technique to quantify the functional group makeup of SOA. We analyzed four functional groups: CO, saturated C–H, unsaturated C–H and O–H. The CO functional group accounted for up to 14% of the phenolic SOA sample mass. Acids measured by ion chromatography account for ∼20% of carbonyl reported by FT-IR.